Introductory biophysics:perspectives on the living state - Claycomb, James; Tran, Jonathan Quoc P. (Boston: Jones and Bartlett Publishers, 2011)
Designed for biology, physics, and medical students, Introductory Biophysics: Perspectives on the Living State, provides a comprehensive overview of the complex subject of biological physics. The companion CD-ROM (eBook version does not include the CD-ROM),, with MATLAB® examples and the student version of QuickField, allows the student to perform biophysical simulations and modify the textbook example files. Included in the text are computer simulations of thermodynamics, astrobiology, the response of living cells to external fields, chaos in population dynamics, numerical models of evolution, electrical circuit models of cell suspension, gap junctions, and neuronal action potentials. With this text students will be able to perform biophysical simulations within hours.
Appendices 1-10, 273-324p.; References 325-338p.; Index 339-359p.
Keywords: Biophysics; Biology